Regularity of Solutions for a Third Order Differential Equation in Hilbert Spaces - Lizama-Yanez, C (2011)
We study regularity of mild and strong solutions of an abstract mathematical model of a flexible space structure under appropriate initial conditions. We apply our results showing qualitative properties of the trajectories in the case of the negative Laplacian operator. © 2011 Elsevier Inc. All rights reserved.
Keywords: Third order Cauchy problems; Regularity of solutions; Mild and strong solutions; Energy functional